Factors behind burnout increase in medical students. Are the criteria so important? - Vale,Thais Campelo Bedê (2021)
Abstract: Introduction: Medical students’ mental health has been a concern to the scientific community, especially as a result of the epidemic of mental comorbidities that have become commonplace among the various social groups in modern society. Objectives: To evaluate the prevalence of Burnout among first- to fourth- year medical students and compare different criteria to define the syndrome. Methods: A total of 511 students from three universities in Brazil answered validated instruments to assess burnout (The Maslach Burnout Inventory) and quality of life (WHOQOL-BREF), and a questionnaire prepared by the authors to assess sociodemographic data Results: There was a prevalence of 31.1% of three-dimensional burnout, 37% of two-dimensional burnout and 44,8% of one-dimensional burnout. There were worse levels of emotional exhaustion among students with two-dimensional burnout, compared to those with only one-dimensional criterion, and worse levels of depersonalization among students with three-dimensional burnout, compared to those with two-dimensional criterion only. The same assessed variables showed correlation with all three criteria. Considering the four domains of quality of life - psychological, physical, environment and social relationships, the psychological and physical domains were the ones that correlated the most to all three aspects of the three-dimensional criteria. Emotional exhaustion was the dimension with the strongest association with three of the four quality of life domains. Conclusions: We question whether the three-dimensional criterion should really be the gold standard to define Burnout.